ADVANCES IN HIGH‐RESOLUTION MALDI MASS SPECTROMETRY FOR NEUROBIOLOGY. Issue 2 (9th November 2020) - DeLaney, Kellen; Phetsanthad, Ashley; Li, Lingjun
Abstract : Research in the field of neurobiology and neurochemistry has seen a rapid expansion in the last several years due to advances in technologies and instrumentation, facilitating the detection of biomolecules critical to the complex signaling of neurons. Part of this growth has been due to the development and implementation of high‐resolution Fourier transform (FT) mass spectrometry (MS), as is offered by FT ion cyclotron resonance (FTICR) and Orbitrap mass analyzers, which improves the accuracy of measurements and helps resolve the complex biological mixtures often analyzed in the nervous system. The coupling of matrix‐assisted laser desorption/ionization (MALDI) with high‐resolution MS has drastically expanded the information that can be obtained with these complex samples. This review discusses notable technical developments in MALDI‐FTICR and MALDI‐Orbitrap platforms and their applications toward molecules in the nervous system, including sequence elucidation and profiling with de novo sequencing, analysis of post‐translational modifications, in situ analysis, key advances in sample preparation and handling, quantitation, and imaging. Notable novel applications are also discussed to highlight key developments critical to advancing our understanding of neurobiology and providing insight into the exciting future of this field. © 2020 John Wiley & Sons Ltd. Mass Spec Rev